2016
DOI: 10.1093/ecco-jcc/jjw007
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis: Serum Infliximab Levels During Maintenance Therapy and Outcomes in Inflammatory Bowel Disease

Abstract: There is a significant difference between serum infliximab levels in patients with IBD in remission, compared with those who relapse. A trough threshold during maintenance > 2 µg/ml is associated with a greater probability of clinical remission and mucosal healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 38 publications
2
54
0
7
Order By: Relevance
“…Studies have found that responders have higher infliximab levels than nonresponders . Several have defined an infliximab therapeutic cut‐off or range that is associated with a specific endpoint . In a retrospective study of secondary loss‐of‐response in IBD, a pre‐dose intensification infliximab trough of ≥3.4 μg/mL was 90% specific for failure to recapture response .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that responders have higher infliximab levels than nonresponders . Several have defined an infliximab therapeutic cut‐off or range that is associated with a specific endpoint . In a retrospective study of secondary loss‐of‐response in IBD, a pre‐dose intensification infliximab trough of ≥3.4 μg/mL was 90% specific for failure to recapture response .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the published literature is with IFX and in general it is accepted (depending on the assay used as a reference) that a trough level of >3 μg/mL is associated with response in patients with luminal CD 35. However, a debate arises whether patients with PFCD would benefit from higher drug levels.…”
Section: Conventional Non-biologic Medical Therapy Biologics and Permentioning
confidence: 99%
“…These patients typically have low infliximab trough levels, suggesting a pharmacokinetic issue . Conversely, high trough levels have been associated with clinical and biochemical remission, C‐reactive protein and faecal calprotectin normalisation, mucosal healing and even fistula healing . Consequently, different strategies have been developed to tackle low trough levels, such as adding azathioprine to infliximab during the most vulnerable period of 6‐12 months after its initiation, a strategy known as combination treatment .…”
Section: Introductionmentioning
confidence: 99%